Analysis of General Input State Dependent Working Vacation Queue with Changeover Time. (23rd April 2014) - Pikkala, Vijaya Laxmi; Vepada, Suchitra
Abstract : We consider a finite bufferG I / M ( n ) / 1 queue with multiple working vacations and changeover time, where the server can keep on working but at a slower speed during the vacation period. Moreover, the amount of service demanded by a customer is conditioned by the queue length at the moment service is begun for that customer. We provide a recursive algorithm using the supplementary variable technique to numerically compute the stationary queue length distribution of the system. Finally, some numerical results of the model are presented to show the parameter effect on various performance measures.